Ethnopedagogy of Turonggo Yakso Dance: Ki Hajar Dewantara's Approach to Cultivating Cultural Literacy in Fourth Grade Elementary School Students: English - Laily Novitasari; Ari Metalin Ika Puspita; Nadi Suprapto (Jurnal Elementaria Edukasia, 2025)
Cultural literacy is important in 21st-century education because it shapes character, national identity, and a reflective attitude towards local values. A study at SDN 1 Gondang, Trenggalek Regency, showed that most students did not understand the philosophical meaning of the Turonggo Yakso Dance, a traditional art form of their region. Teachers also have not utilized this dance as a learning resource, even though the school is located at the center of cultural preservation. This study aims to describe the improvement of cultural literacy of fourth-grade students through the application of Turonggo Yakso Dance Ethnopedagogy. The method used was descriptive qualitative with observation, interview, and documentation techniques. The results showed that the application of Ethnopedagogy with the principles of Ki Hajar Dewantara's 5N made learning more contextual and meaningful. Students better understand cultural values, the spirit of togetherness, and local identity. In addition to enhancing cultural literacy, this learning also supports the achievement of the Sustainable Development Goals (SDGs), namely SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), SDG 11 (Sustainable Cities and Human Settlements), and SDG 16 (Peace, Justice, and Resilient Institutions)